Dynamic of Carbon, Nitrogen Content and Biomass Production of Axonopus compressus on Modified Shade Conditions of Oil Palm Plantation - Martaguri, I.; Karti, P.D.M.H.; Wiryawan, K.G.; Dianita, R.; Abdullah, L. (Pakistan Journal of Nutrition, 2016)
Background: Beside as a source of energy for ruminants, grasses have been identified having a capacity as carbon storage. Axonopus compressus is a grass species that mostly found under shade condition of palm plantations and are easily adaptable with the ecosystem. As a part of the ecosystem, the grass would always carry on photosynthesis even under shade condition as encountered by Axonopus compressus. Thus, it might play an important role in storing carbon. Methodology: Therefore, in this study the capability of this grass in storing carbon were investigated including carbon storage dynamics, nitrogen content, C/N ratio and biomass production. In advanced, carbon and nitrogent content of soil were also studied. A completely randomized design was utilized as experimental design with different grass age of 10, 20, 30, 40, 50 and 60 days as the treatments. Results: Results indicated that grass age influenced significantly all parameters except carbon and nitrogen content as well as the C/N ratio of soil. Furthermore, it was also revealed that there is a dynamic of carbon storage in leaf, stemp and root of the grass. Conclusion: The capacity of the grass in storing carbon increased with increasing plant age.